Exploring Senior High School Students’ Needs for Literature-Based Learning Materials to Teach Narrative Text - Dhea Aulia Nurita Hanung; Munfangati, Rahmi (ELLITE: Journal of English Language, Literature, and Teaching, 2024)
Literature offers rich linguistic input and meaningful contexts that can enhance students’ language engagement and acquisition. This study aims to explore students’ needs in speaking materials using narrative text literature. Using a mixed methods approach, data was collected through interviews and observations involving teachers as well as 8th grade students. There were 3 students interviewed, and 30% of the total students were given a questionnaire. The results found that students need pronunciation and fluency skills, but there is a gap between students’ abilities and the skills they need so they want communicative learning activities such as discussion, storytelling, and roleplay to improve speaking skills. In addition, students also need teaching materials that are comprehensive, relevant, and supported by audiovisual media and interactive activities to improve their skills and understanding of narrative texts. This study concludes that the development of teaching materials based on these needs can improve the quality of narrative text learning.